THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, EMPLOYEE ENGAGEMENT, AND WORK ENVIRONMENT, ON THE PERFORMANCE OF EMPLOYEES WITH WORK DISCIPLINE AS INTERVENING AT THE GENERAL BUREAU OF THE REGIONAL SECRETARIAT OF RIAU ISLANDS PROVINCE - Atik, Atik; Indrayani, Indrayani; Khaddafi, Muammar; Titik Windayati, Diana (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to determine the effect of transformational leadership, employee engagement, and work environment on the performance of employees with work discipline as an intervening variable at the General Bureau of the Regional Secretariat of the Riau Archipelago Province. The research method used is a descriptive method with a quantitative approach. This descriptive method involves collecting data to test hypotheses or answer questions about people's opinions on an issue or topic. Data collection was carried out using a questionnaire instrument which was distributed to 112 respondents. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 4 software. Transformational leadership influences employee work discipline. Transformational leadership influences employee work performance. Employee Engagement has no significant effect on work discipline. Employee Engagement has no significant effect on employee performance. The work environment affects the work discipline of employees. Work environment has no significant effect on employee performance. Work discipline affects employee performance. The work discipline variable is able to mediate the effect of transformational leadership on performance. The work discipline variable is not able to mediate the influence between Employee Engagement on Employee Performance. The work discipline variable is unable to mediate the influence of the work environment on employee performance. The work environment affects the work discipline of employees. Work environment has no significant effect on employee performance. Work discipline affects employee performance. The work discipline variable is able to mediate the effect of transformational leadership on performance. The work discipline variable is not able to mediate the influence between Employee Engagement on Employee Performance. The work discipline variable is unable to mediate the influence of the work environment on employee performance. The work environment affects the work discipline of employees. Work environment has no significant effect on employee performance. Work discipline affects employee performance. The work discipline variable is able to mediate the effect of transformational leadership on performance. The work discipline variable is not able to mediate the influence between Employee Engagement on Employee Performance. The work discipline variable is unable to mediate the influence of the work environment on employee performance. The work discipline variable is not able to mediate the influence between Employee Engagement on Employee Performance. The work discipline variable is unable to mediate the influence of the work environment on employee performance. The work discipline variable is not able to mediate the influence between Employee Engagement on Employee Performance. The work discipline variable is unable to mediate the influence of the work environment on employee performance.